Reforms in Muslim Personal Law: Dissolution of Muslim Marriage Act 1939 - Bhardwaj, Karuna; Hudda, Himanshi (International Journal of Research in Interdisciplinary Studies, 2023)
Every law must be revised to adapt it over time. So are Islamic personal laws. The Islamic Personal Law (Shariat) Application Act 1937 states that the personal affairs of certain Muslims are governed by their pure Sharia law. Several important provisions such as inheritance, childcare and custody, dissolution of marriage, polygamy, etc. have been modified, supplemented or reformed by both state laws and legal precedents. These reforms caused significant changes in the interpretation, application and interpretation of classical Islamic law. In many cases, the reforms so far deviate from the classical laws in these matters. This article attempts to examine and analyze these reforms based on whether they are compatible with Islamic legal sources.